Decoders For MTS Radars - Woodman Pollitt, Ronald Francisco (1981)
Different coding schemes, their advantages, and the need for the use of pbase coded pulses is discussed by Farley (page 410, this volume). Here we shall limit ourselves to describe decoding techniques and equipment which has been used by MST radars and briefly present some recommendations for new systems. Decoding can be done either by software in special-purpose (array processors, etc.) or .general-purpose computers or in specially designed digital decoders.